AB0414 Claims Database Analysis of Adherence to Adalimumab Therapy and Health Care Costs for Patients with Rheumatoid Arthritis. (10th June 2014) - Liu, Y.; Tundia, N.; Skup, M.; Ayyagari, R.; Du, E.X.; Chao, J.; Mulani, P.; Bao, Y.
Abstract : Background: We examined the relationship between adherence to adalimumab (ADA), an injectable tumor necrosis factor alpha inhibitor, and health care costs for patients with rheumatoid arthritis (RA). Methods: Adult patients (≥18 years old) with RA (International Classification of Diseases-9 714.0x) and ≥1 claim for ADA were identified in the Truven Health MarketScan® Databases. Patients were required to have ≥6 months of continuous eligibility of health care coverage before initiation of ADA (baseline period), ≥12 months of continuous eligibility after initiation of ADA (study period), and >90 days of ADA treatment after initiation. Adherence was measured in terms of the proportion of days covered (PDC), defined as the proportion of the study period during which patients were covered by ADA prescriptions. Patients were considered adherent if their PDC exceeded 0.8. Health care costs included medical costs (inpatient, emergency department, and outpatient visits), pharmacy costs (associated with pharmacy claims), and total costs (medical + pharmacy). Adherence, health care costs, and the effect of adherence on cost savings were assessed at state and national levels. Multivariate regression models, adjusting for patient-level baseline confounding factors, were used to estimate PDC levels, costs, and expected cost savings associated with improvement in ADA adherence. Results: The sample consisted of 14, 105 patients with RA. Mean age was 53 years, 74% were women, and 29% had prior treatment with biologics. The average PDC among patients was 0.756, and 57% of patients were adherent. Nationwide estimates of total per-patient annual costs were 17, 962 without ADA and 31, 487 including ADA. Multivariate regression analyses estimated that on average, a 10% absolute increase in PDC (i.e., from 0.756 to 0.832) was associated with a decrease in annual medical and pharmacy (excluding ADA) costs of 1, 486 and 517 per patient, respectively, which offsets a majority of the increase in ADA cost due to better adherence (2, 222). Conclusions: This study demonstrated that although better adherence increased ADA costs, increased costs were partially offset by savings in medical cost. Acknowledgements: The design, study conduct, and financial support for the study/trial were provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. All authors contributed to the development of the publication and maintained control over the final content. Cathryn Carter, MS, of Arbor Communications provided medical writing and editing services in the development of this abstract. Financial support for these services was provided by AbbVie. Disclosure of Interest: Y. Liu Employee of: University of Missouri–Kansas City, N. Tundia Shareholder of: AbbVie, Employee of: AbbVie, M. Skup Shareholder of: AbbVie, Employee of: AbbVie, R. Ayyagari Employee of: Analysis Group, which received payment from AbbVie to assist with abstract preparation, E. X. Du Employee of: Analysis Group, which received payment from AbbVie to assist with abstract preparation, J. Chao Shareholder of: AbbVie, Employee of: AbbVie, P. Mulani Shareholder of: AbbVie, Employee of: AbbVie, Y. Bao Shareholder of: AbbVie, Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.2287